Archie Asbridge setting up a program to measure the vertical ozone profile - (Creator); (Contributor) (1965)
Archie writes: This is approximately late 1965 when I was visiting Resolute Bay and setting up a program to measure the vertical ozone profile using balloon borne ozonesondes, which is what you see in the picture.